A Mechanism‐Based Pharmacokinetic/Pharmacodynamic Model for Bococizumab, a Humanized Monoclonal Antibody Against Proprotein Convertase Subtilisin/Kexin Type 9, and Its Application in Early Clinical Development. (9th February 2017) - Udata, Chandrasekhar; Garzone, Pamela D.; Gumbiner, Barry; Joh, Tenshang; Liang, Hong; Liao, Kai‐Hsin; Williams, Jason H.; Meng, Xu
Abstract: Bococizumab (RN316/PF‐04950615), a humanized monoclonal antibody, binds to secreted proprotein convertase subtilisin/kexin type 9 (PCSK9) and prevents its downregulation of low‐density lipoprotein receptor, leading to improved clearance and reduction of low‐density lipoprotein cholesterol (LDL‐C) in plasma. A mechanism‐based drug‐target binding model was developed, accounting for bococizumab, PCSK9, and LDL‐C concentrations and the effects of concomitant administration of statins. This model was utilized to better understand the pharmacokinetic/pharmacodynamic (PK/PD) data obtained from 3 phase 1 and 2 phase 2a clinical studies. First, simulations performed with this model demonstrated that the conventional method of the area‐under‐the‐curve ratio for bioavailability determination underestimated the subcutaneous bioavailability of bococizumab due to its target‐mediated disposition. Second, a covariate model component for statin effects on bococizumab PK/PD was characterized, including a description of the decreased baseline LDL‐C, increased baseline PCSK9, and increased LDL‐C lowering with concomitant use of statins. Last, the impact of the dosing regimens with and without a dose holiday on bococizumab's LDL‐C–lowering effectiveness was shown to be predictable due to the well‐characterized PK‐PD relationship.